Sales Growth dan Tax Avoidance dengan Kepemilikan Institusional Sebagai Variabel Pemoderasi - Nora Safitri; Theresia Woro Damayanti (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
Tax is an instrument that is needed in reducing the gap of state revenue, but, in fact, the tax revenue hasn’t reached the target yet due to tax avoidance. Tax avoidance is an arrangement to minimize or eliminate the tax burden borne. Some companies think that doing tax avoidance is a legal practice. Sales growth is important in a company, especially in working capital management, so the company can predict how much profit has been generated. However, whenever getting large profit, companies still practice tax avoidance. The existence of institutional ownership in the company can lead to a strict supervisory attitude towards management performance, so that the company performance increases and reduces the possibility of tax avoidance practices. The purpose of this study is to determine whether sales growth affects tax avoidance with institutional ownership as a moderating variable. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange in the period 2010-2017 obtained using the purposive sampling method. Data analysis uses descriptive statistics, stationarity test, and panel data regression analysis. The results showed that sales growth positively influenced tax avoidance